Quantitative magnetic analysis reveals ferritin-like iron as the most predominant iron-containing species in the murine Hfe-haemochromatosis - Gutiérrez, Lucía; Spasić Vujić, Maja; Muckenthaler, Martina (Biochimica et biophysica acta. Molecular basis of disease, 2012)
Quantitative analysis of the temperature dependent AC magnetic susceptibility of freeze-dried mouse tissues from an Hfe hereditary haemochromatosis disease model indicates that iron predominantly appears biomineralised, like in the ferritin cores, in the liver, the spleen and duodenum. The distribution of the amount of ferritin-like iron between genders and genotypes coincides with that of elemental iron and nonheme iron. Importantly, the so-called paramagnetic iron, a quantity also determined from the magnetic data and indicative of nonmineralised iron forms, appears only marginally increased when iron overload takes place.
Gesehen am 17.08.2018